PROCEDURE OF MULTI SLICE COMPUTED TOMOGRAPHY (MSCT) THORAX EXAMINATION USING POSITIVE CONTRAST MEDIA WITH BREAST CANCER CASE - Janita Limbong, Rosari; Masrochah, Siti; Sulaksono, Nanang (Perhimpunan Radiografer Indonesia (PARI), 2021)
Background: The protocol for MSCT Thorax examination is axial/coronal/sagittal. The slice thickness parameter has an important role in examining MSCT Thorax in breast cancer cases using contrast media. The thinner the slice thickness, the better the detailed image obtained. The aim of this study is to explain the MSCT Thorax examination procedure in breast cancer cases using positive contrast media, the role of slice thickness in diagnosis and to find out diagnostic information on the MSCT Thorax examination in cancer cases breast. Methods: This type of research is qualitative with a literature study approach. The data were obtained by identifying the problem then looking for keywords, namely MSCT Thorax, Slice thickness, breast cancer. Literature reviews are carried out through journal search engine searches, such as: Google Scholar, American Journal Rontgenology (AJR), Pubmed, Proquest. The collected journals are reduced based on inclusion criteria so that 3 relevant journals are obtained then analyzed descriptively so that they can answer the objectives to be drawn conclusions. Results: The results of a literature study show that the MSCT Thorax examination procedure in cases of breast cancer using contrast media is fasting 6 hours before the examination, laboratory checks (urea cratinin within normal limits), releasing all metals in the body, CT scan plane, fixation tools, blankets. , contrast media, injector set. Conclusion: Contrast media dosage 1-2 ml / kg body weight, flow rate 2-4 ml / s, concentration 300-350 mgl / ml, patient position supine feet first, upper limit of lung Apex and lower limit of diaphragm (depending on needs), axial cut, coronal, sagittal, the parameters used were kV, mAs, slice thickness, matrix, WW, WL. A thin slice thickness will provide more accurate diagnostic information and a clear picture of metastases and small lesions can be seen.